Decellularized brain matrix enhances macrophage polarization and functional improvements in rat spinal cord injury - Hong, Jin Young; Seo, Yoojin; Davaa, Ganchimeg; Kim, Hae-Won; Kim, Soo Hyun; Hyun, Jung Keun (ELSEVIER SCI LTD, 2020)
Spinal cord injury (SCI) is a devastating lesion lacking effective treatment options currently available in clinics. The inflammatory process exacerbates the extent of the lesion through a secondary injury mechanism, where proinflammatory classically activated macrophages (M1) are prevalent at the lesion site. However, the polarized alternatively activated anti-inflammatory macrophages (M2) are known to play an important role in wound healing and regeneration following SCI. Herein, we introduce porcine brain decellularized extracellular matrix (dECM) to modulate the macrophages in the injured spinal cord. The hydrogels with collagen and dECM at various dECM concentrations (1, 5, and 8 mg/ml) were used to cultivate primary macrophages and neurons. The dECM hydrogels were shown to promote the polarization of macrophages toward M2 phase and the neurite outgrowth of cortical and hippocampal neurons. When the dECM hydrogels were applied to rat SCI models, the proportion of Ml and M2 macrophages in the injured spinal cord was substantially altered. When received dECM concetration of 5 mg/ml, the expression of molecules associated with M2 (CD206, arginasel, and IL-10) was significantly increased. Consistently, the population of total macrophages and cavity area were substantially reduced in the dECM-treated groups. As a result, the locomotor functions of injured spinal cord, as assessed by BBB and ladder scoring, were significantly improved. Collectively, the porcine brain dECM with optimal concentration promotes functional recovery in SCI models through the activation of M2 macrophages, suggesting the promising use of the engineered hydrogels in the treatment of acute SCI. Statement of significance Spinal cord injury (SCI) is a devastating lesion, lacking effective treatment options currently available in clinics. Here we delineated that the treatment of injured spinal cord with porcine brain decellularized matrix-based hydrogels for the first time, and could modulate the macrophage polarization and the ultimate functional recovery. When appropriate formulations were applied to a contused spinal cord model in rats, the decellularized matrix hydrogels shifted the macrophages to polarize to pro-regenerative M2 phenotype, decreased the size of lesion cavity, and finally promoted the locomotor functions until 8 weeks following the injury. We consider this work can significantly augment the matrix(biomaterial)based therapeutic options, as an alternative to drug or cell-free approaches, for the treatment of acute injury of spinal cord. (C) 2019 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: INFLAMMATORY RESPONSE; M2 MACROPHAGES; ECM HYDROGEL; AXON GROWTH; PROMOTES; RECOVERY; ANGIOGENESIS; OSTEOPONTIN; ACTIVATION; PLASTICITY